THE EFFECT OF EXCHANGE RATES AND INFLATION ON THE MONEY SUPPLY IN INDONESIA: AN AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) APPROACH - Misbachudin; Fakhri Ahmad Zainunnuri; Neng Ulpa Apipah; Syaeful Bakhri; Abdul Aziz (RADJA PUBLIKA, 2026)
This study aims to analyze the effects of inflation and exchange rates on the money supply in Indonesia and to identify the short-term and long-term relationships among these variables. A country’s economic stability is inextricably linked to the dynamics of inflation, exchange rates, and the money supply, which are interrelated within the economic system. This study employs a quantitative approach using secondary data obtained from Bank Indonesia and the Central Statistics Agency (BPS) for the period 2020-2024. The analysis method used is the Autoregressive Distributed Lag (ARDL) model, as it is capable of estimating both short-term and long-term relationships simultaneously within a single model. The results indicate a long-term relationship among inflation, exchange rates, and the money supply. Partially, the exchange rate has a positive and significant effect on the money supply in Indonesia. This suggests that changes in the exchange rate particularly when the rupiah depreciates can drive increased liquidity in the economy through monetary policy mechanisms and international trade activities. Meanwhile, inflation does not have a significant effect on the money supply in the short term. This indicates that changes in inflation during the study period did not directly influence money supply policy due to the inflation control policies implemented by Bank Indonesia. Thus, exchange rate stability is a critical factor that must be considered in maintaining monetary equilibrium and national economic stability. Keywords: Exchange Rate, Inflation, Money Supply, Monetary Policy, ARDL